KOMUNIKASI DAKWAH EFEKTIF DALAM PERSPEKTIF ALQURAN - Markarma, Andi (Hunafa: Jurnal Studia Islamika, 2014)
In the Koran perspective, the effective da'wah communication  (qaulan balīghan) is highly recommended. The ability  or a preacher to communicate effectively can affect the relative truth of thought of  the audience or mustami’ (listeners). The Koran insists that Islam is a perfect religion and must be socialized and internalized into the minds of its adherents in order to understand and to implement it consistently and cuntinually. The da’I must possess a good mastery of communication, in Arabic, qaulan balīghan, in order to be able to internalize the teachings of Islam into the minds of its adherents, through which they will behave as true Muslims.Kata Kunci: dakwah, komunikasi, perspektif Alquran ansifga:@:mso-fareast-language:EN-US;mso-bidi-language:AR-SA'>:        Corak, quasi-Obyektifis Tradisionalis, Obyektifis, quasi Obyektifis Modernis